Contextual Reading of QS. Al-Baqarah [2]: 222 with the Ma'na Cum Maghza Approach - Hana, Rima Rayhana; Akhmad Dasuki; Munirah; Badarulzaman, Muhammad Hafiz (QOF, 2023)
This article examines the meaning of the term i’tizāl in QS. Al-Baqarah [2]: 222 using the analysis of ma’na cum maghza. In this verse, the word i’tizāl is juxtaposed with the word al-maḥīḍ, indicating the command for husbands to abstain from approaching their wives during menstruation. This research involves literature review. The ma’na cum maghza analysis is employed to explore the historical meaning (al-ma’nā at-tārikhī), the historical context (al-maghzā al-tārikhī), and its contextualization into a dynamic meaning (al-maghzā al-mutaḥarrik). The findings indicate that, from a historical perspective, the verse commands avoidance of the menstruation site (al-maḥiḍ), emphasizing abstaining from sexual relations during menstruation rather than avoiding the menstruating wife (al-hāid), as practiced in ancient traditions. The command to abstain (fa’tazilū) is rooted in the inherent pain (adha) of menstruation for women. Historically, the verse signifies (1) the high status of women, (2) the need for protection against physical and mental illnesses, and (3) the importance for spouses to responsibly control reproductive organs for both health and religious reasons. From a dynamic perspective, the verse highlights the significance of reproductive health, crucial for human survival and lineage preservation (hifz al-nasl). Therefore, in other situations such as when a woman experiences abnormal bleeding (istiḥāḍah) or when the husband faces reproductive disorders and sexually transmitted diseases, the command to abstain from intercourse applies, considering its potential negative impacts.